Exploring The Challenges in Intervention Programs for Speech Sound Disorders: A Systematic Review - Wibawati, Restu Wahyu; Muryanti, Muryanti; Susanti, Nadya (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Speech Sound Disorders (SSD) are among the most common communication problems treated by speech-language therapists. Despite its high prevalence, intervention remains challenging due to diverse error patterns, limited resources, and varying clinical decision-making. Objectives: This study aims to identify challenges in SSD intervention programs through a systematic review, providing insight to strengthen clinical practice and guide future research. Methods: A systematic review was conducted following PRISMA guidelines. Articles published between 2015–2025 were retrieved from Google Scholar, PubMed, ScienceDirect, and manual searches using predetermined keywords. Inclusion criteria consisted of full-text English studies reporting challenges in SSD intervention, while effectiveness trials and conceptual-only literature were excluded. Results: Nine studies met the criteria. Four major challenges were identified: (1) limited intervention intensity; (2) clinical decision-making influenced more by therapist experience and context than by structured evidence; (3) low implementation of evidence-based approaches; and (4) inconsistent assessment tools and limited home practice support. These barriers impact diagnosis accuracy, target selection, and treatment outcomes. Conclusion: SSD intervention faces clinical, practical, and institutional barriers. Strengthening evidence-based practice, improving assessment consistency, and optimizing support systems—including parent involvement—may enhance service quality and outcomes. Keywords: Speech sound disorders, Articulation intervention, Phonological intervention, Clinical practice, Systematic review